Uji Beda Sebelum dan Sesudah Penerapan Sistem Baru Pada Pelayanan Jasa Bongkar Muat Barang di Pt. Samudra Indah Sejahtera Semarang - Retno Anggoro; Septina Dwi Retnandari; Endra Winarni (Jurnal Maritim Polimarin, 2018)
The purpose of this study was to determine the difference between before and after the implementation of the new system in loading and unloading services at PT. Samudra Indah Sejahtera Semarang. The new system implemented in the company is inaportnet system. It would find out whether there are developments in the quantity and quality of the number of customers and services by the company. Sample from this study is consumers owned by PT. Samudra Indah Sejahtera as many as 25 companies. The results were analyzed statistically to look for the differences between the condition. This quantitative research used non-parametric test for two two independent samples, using the Kolmogorov Smirnov Test formula. The finding is there is no difference between before and after the implementation of a new system. It means that the implementation of a new system does not have a significant effect on services provided related to reliability factors. The application of a new system does not significantly affect the service provided in factors of responsiveness, assurance, and empathy.